Handbook of computability theory - Griffor, Edward R. (Studies in logic and the foundations of mathematics, 1999)
Part 1: Fundamentals of Computability Theory. -- Part 2: Reducibilities and Degrees. -- Part 3: Generalized Computability Theory. -- Part 4: Mathematics and Computability Theory. -- Part 5: Logic and Computability Theory. -- Part 6: Computer Science and Computability Theory
Includes bibliographical references and indexes. - Description based on print version record
Keywords: Electronic books; Aufsatzsammlung; Berechnungstheorie